PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP DUNIA PENDIDIKAN (STUDI LITERATUR) - Angely Noviana Ramadani; Kartika Chandra Kirana; Astuti, Umi; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to determine the effect of the use of social learning media in the world of education. Learning media is a tool used by teachers to convey learning messages to their students so that the learning messages reach students properly. The use of learning media also greatly influences students, which makes it easier for students to understand the aims and objectives of learning materials, and students can also develop curiosity and gain more real knowledge with the learning carried out. This study uses a quantitative approach, in which this quantitative research aims to describe and elaborate on an influence on the use of instructional media in the world of education. The technique used in this data research is library research, in which this literature study is a study that collects research materials related to books, scientific journals, publications, and literature, which can be used as a basis for research sources to be examined by the author, by means of describe the data and describe the data used through several expert opinions. The variables used in this assessment use independent variables and dependent variables. The variables in this study are anything in any form determined by the researcher to be studied so that information can be obtained about these matters which are then drawn conclusions. So in this study using a qualitative approach this research can be expected to provide comprehensive facts about the influence of the use of instructional media in the world of education. The benefit in writing this research is to add knowledge and insight to readers and to know how important learning media is in the world of education.